2020
DOI: 10.29065/usakead.684766
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen ve Öğretmen Adaylarının Stem Alanlarına Yönelı̇k Tutumlarının ve Stem Öğretı̇mı̇ Yönelı̇mlerı̇nı̇n Farklı Değı̇şkenler Açısından İncelenmesı̇

Abstract: Özet: Günümüzde STEM (Bilim, Teknoloji, Mühendislik ve Matematik) eğitiminin asıl uygulayıcısı olan öğretmenlerin derslerine STEM'i entegre etmelerine yönelik neler yapılabileceğini ortaya koyabilmek için, öncelikle var olan durumun cinsiyet, branş, kıdem yılı ve hizmet içi eğitim alma durumu gibi değişkenler açısından betimlenmesi önemlidir. Bu araştırmadan elde edilen veriler kullanılarak, öğretmenlere göre STEM eğitimleri planlanabilir. Bu nedenle çalışmanın amacı, Ege bölgesinde yer alan bir il merkezindek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In his study, Çayak (2019) concluded that the mean scores of male teachers on the STEM-TPACK sub-dimensions of the gender variable were higher and differentiated than female teachers. Similarly, Gedik, Sönmez, and Yeşiltaş (2019) concluded that pre-service primary school teachers' technological pedagogical content knowledge competencies differed in favor of male pre- 2021), on the other hand, concluded that the mean score of female teachers was higher than the mean score of male teachers regarding gender in mathematics teachers' knowledge of STEM-based education, while Hiğde et al (2020) concluded that the STEM teaching orientations of teachers and pre-service teachers and their attitudes towards STEM fields did not differ according to gender. Furthermore, unlike Rahman et al (2022), their study with secondary school teachers concluded that non-parametric analysis did not show a difference in STEMPCK scores based on gender, educational qualification, and teaching experience.…”
Section: Results Related To Pre-service Primary School Teachers' View...mentioning
confidence: 99%
“…In his study, Çayak (2019) concluded that the mean scores of male teachers on the STEM-TPACK sub-dimensions of the gender variable were higher and differentiated than female teachers. Similarly, Gedik, Sönmez, and Yeşiltaş (2019) concluded that pre-service primary school teachers' technological pedagogical content knowledge competencies differed in favor of male pre- 2021), on the other hand, concluded that the mean score of female teachers was higher than the mean score of male teachers regarding gender in mathematics teachers' knowledge of STEM-based education, while Hiğde et al (2020) concluded that the STEM teaching orientations of teachers and pre-service teachers and their attitudes towards STEM fields did not differ according to gender. Furthermore, unlike Rahman et al (2022), their study with secondary school teachers concluded that non-parametric analysis did not show a difference in STEMPCK scores based on gender, educational qualification, and teaching experience.…”
Section: Results Related To Pre-service Primary School Teachers' View...mentioning
confidence: 99%